2018
DOI: 10.3892/etm.2018.6483
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary actinomycosis diagnosed by transbronchoscopic lung biopsy: A case report and literature review

Abstract: Pulmonary actinomycosis is a chronic, suppurative, granulomatous disease caused by Actinomyces israelii, an obligate anaerobe. The clinical manifestations and imaging characteristics of pulmonary actinomycosis lack specificity and can lead to confusion with tuberculosis and lung cancer. The present study reported a case of pulmonary actinomycosis diagnosed by transbronchoscopic lung biopsy and reviewed the literature on the disease. The clinical characteristics, signs, laboratory findings as well as progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…Suzuki et al [7] reported a case where pulmonary actinomycosis was diagnosed by transbronchial lung biopsy, but it is to remember that the diagnosis was made based on the tissue histopathological examination, not the cultures. Ding et al [5] and Tabarsi et al [8] presented similar cases. In our patient, bronchoscopy was not performed because the disease process seemed to originate from the chest wall.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Suzuki et al [7] reported a case where pulmonary actinomycosis was diagnosed by transbronchial lung biopsy, but it is to remember that the diagnosis was made based on the tissue histopathological examination, not the cultures. Ding et al [5] and Tabarsi et al [8] presented similar cases. In our patient, bronchoscopy was not performed because the disease process seemed to originate from the chest wall.…”
Section: Discussionmentioning
confidence: 69%
“…It may also involve the central nervous system, bones and joints and the genitourinary system [4]. Lung in-fection occurs as a result of aspiration of infected contents from the oral cavity and the gastrointestinal tract [5]. Risk factors include lack of proper oral hygiene, alcoholism, chronic respiratory diseases such as chronic obstructive pulmonary disease, bronchiectasis, history of pulmonary tuberculosis, immunosuppression in the course of other diseases or treatment [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men are twice more affected than women. [ 4 ] Poor oral hygiene, alcoholism, immunosuppressive conditions, diabetes, and underlying structural lung diseases such as emphysema, chronic bronchitis, and bronchiectasis can predispose for infection. [ 5 6 ] They are commensals seen in the mucosal lining of the oropharynx, gastrointestinal tract, and female genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations and imaging characteristics of pulmonary actinomycosis lack specificity, and can lead to confusion with tuberculosis and lung cancer. This may lead to misdiagnosis of the disease, and hence, incorrect treatment [11]. Cases of musculoskeletal actinomycosis, such as that of the long bones are rare, and are typically described as chronic sclerotic or spherical osteomyelitis [12].…”
Section: Introductionmentioning
confidence: 99%